Topology and acylation of spiralin. - Wróblewski, H (1989)
Of the 51 polypeptides detected by sodium dodecyl sulfate-polyacrylamide gel electrophoresis in the plasma membrane of the helical mollicute Spiroplasma melliferum, 21 are acylated, predominantly with myristic (14:0) and palmitic (16:0) chains. This is notably the case for spiralin, the major membrane protein of this bacterium, which contains an average of 0.7 acyl chains per polypeptide, attached very probably by ester bonds to alcohol amino acids. The amphiphilicity of spiralin was demonstrated by the behavior of the protein in charge-shift electrophoresis, its incorporation into liposomes, and its ability to form in the absence of lipids and detergents, globular protein micelles (diameter, approximately 15 nm). The presence of epitopes on the two faces of the cell membrane, as probed by antibody adsorption and crossed immunoelectrophoresis, and the strong interaction between spiralin and the intracytoplasmic fibrils show that spiralin is a transmembrane protein. The mean hydropathy of the amino acid composition of spiralin (-0.30) is on the hydrophilic side of the scale. Surprisingly, the water-insoluble core of spiralin micelles, which is the putative membrane anchor, has a still more hydrophilic amino acid composition (mean hydropathy, -0.70) and is enriched in glycine and serine residues. Taking into account all these properties, we propose a topological model for spiralin featuring a transbilayer localization with hydrophilic domains protruding on the two faces of the membrane and connected by a small domain embedded within the apolar region of the lipid bilayer. In this model, the membrane anchoring of the protein is strengthened by a covalently bound acyl chain.